Impact of COVID-19 program adaptations on costs and cost-effectiveness of community management of acute malnutrition program in South Sudan - Kemish Kenneth Alier; Hannah Tappis; Sule Ismail; Shannon Doocy (Public Health Nutrition, 2024)
Abstract